Fuel Cells: Three‐Dimensional Interlocking Interface: Mechanical Nanofastener for High Interfacial Robustness of Polymer Electrolyte Membrane Fuel Cells (Adv. Mater. 2/2017). Issue 2 (January 2017) - Yuk, Seongmin; Choo, Min‐Ju; Lee, Dongyoung; Guim, Hwanuk; Kim, Tae‐Ho; Lee, Dai Gil; Choi, Sungyu; Lee, Dong‐Hyun; Doo, Gisu; Hong, Young Taik; Kim, Hee‐Tak
Abstract : In article 1603056, Y. T. Hong, H.‐T. Kim, and co‐workers present a three‐dimensionally interlocked interfacial layer as a nanofastener for high interfacial robustness of a hydrocarbon membrane‐based polymer electrolyte fuel cell, which features an interconnected ball‐and‐socket joint structure. The interlocking interface provides an unprecedented level of interfacial durability and improved humidity cycle durability of the fuel cell by 20 times.